A numerical study of heat transfer in fin?tube heatexchangers using winglet-type vortex generators in common-flow down configuration. (29th August 2007) - Tiwari, S.; Prasad, P. L. N.; Biswas, G.
Numerical investigation of flow and heat transfer in a rectangular duct with a built-in circular tube in the presence of delta-winglet type vortex generators has been carried out for moderate Reynolds numbers and three different angles of attack of the winglets (24?, 30? and 34?). The investigation is necessitated by the need to enhance heat transfer on the gas side of the fin-tube heat exchangers through generation of streamwise longitudinal vortices. The strategy for heat transfer enhancement involves introduction of a strong swirling motion in the flow field. The swirling motion can be generated by the longitudinal vortices. In the present study, the longitudinal vortices have been created by the delta-winglet type vortex generators in common-flow-down configuration. The vortex generators are mounted behind the tubes. An element of a heat exchanger has been considered for detailed study of the flow structure and heat transfer analysis. The present numerical study is limited to isothermal fins, single row of tubes and laminar flow situations. The analysis can easily be extended to multiple rows of tubes. It has been separately verified that the flow situation retains its laminar nature for the range of Reynolds number considered in the present problem. Hence the heat transfer analysis does not use any turbulence model in the present investigation. The consequences of employing these vortex generators are a significant separation delay and removal of the zone of poor heat transfer from the near-wake of the tubes. The heat transfer in the near-wake region can be enhanced as high as 230%. Results also show a marked increase in overall heat transfer in the channel.